Economic Drivers of Technology Enabled Health Services - Chandrasekaran, N.; A. Indira (European Journal of Multidisciplinary Studies, 2017)
Technology is all pervasive today. Advancements in technology has been welcomed and applauded in the health care sector. Healthcare technologies involve both clinical as well as well as non clinical processes. The applications involve patient safety, disease surveillance, E-health records, and patient empowerment. There are now various firms which are building health applications to further help the patients, care-givers and doctors. The global economy has however seen a change in the aftermath of 2008. The downturn experienced seemed to continue well into 2017. There however seems to be a spirited feeling that the economy is on the up and better prospects are forecasted for 2018. In this background, this paper looks at the various economic factors that impact technology enabled health services.